SOCIO-PRAGMATIC ANALYSIS OF PROHIBITION UTTERANCES IN ARISTOCRATIC MOVIE MANUSCRIPTS - HIDAYATI , ANI DWI NAZILAH (2007)
This research paper entitled "A sociopragmatic analysis of prohibition utterances in aristocratic movie manuscripts". The problems of research are to find the types of prohibition, the pattern of politeness uses in employing prohibition and the implicature of prohibition utterances. So the objective of the study are to identify the type of prohibition used in movie manuscripts, to identify the pattern of politeness used in movie manuscripts, and to describe the implicature of prohibition utterances. To answer those problems, this research uses document and observation as the method of data collection. The sources of the data are taken from "Ever After" and "Man in the Iron Mask" movie manuscripts. This research employs the sociopragmatic analysis, especially, the types of prohibition utterances by Hornby and Etherton, the politeness strategy by Brown and Levinson, and the implicature by Grice. The result of the study shows that first, there are six types of prohibition. One of them has not yet classified by Hornby and Etherton. That is prohibition that using "can't + infinitive without "to"". Second, in employing prohibition the speaker uses four pattern of politeness strategy, that is baldly on- record, positive politeness, negative politeness and off-record. Third, the prohibition utterances have implicature as giving suggestion, showing solidarity, showing refusal, showing Allusions, warning, wish, requesting.